2017
DOI: 10.4155/fsoa-2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Phosphorylated TDP-43: An Exploratory Study for a Peripheral Surrogate Biomarker Development for Alzheimer’s Disease

Abstract: Aim:Alzheimer's disease (AD) and other forms of dementia create a noncurable disease population in world's societies. To develop a blood-based biomarker is important so that the remedial or disease-altering therapeutic intervention for AD patients would be available at the early stage.Materials & methods:TDP-43 levels were analyzed in postmortem brain tissue and platelets of AD and control subjects.Results:We observed an increased TDP-43 (<60%) in postmortem AD brain regions and similar trends were also observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Some reports also recently discovered that platelets contain a proteolytic system by which hemostasis and thrombosis is acquired [17,18] . Since we have shown that an elevation of pathological pTDP43 within the platelet cytosol is correlated to hippocampal cortex of AD patients [13] , it was imperative that we analyze these platelet proteolytic systems. We attempted to establish any change of the protein concentrations of proteolytic system, since platelet proteasome concentrations have not been reported prior to our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports also recently discovered that platelets contain a proteolytic system by which hemostasis and thrombosis is acquired [17,18] . Since we have shown that an elevation of pathological pTDP43 within the platelet cytosol is correlated to hippocampal cortex of AD patients [13] , it was imperative that we analyze these platelet proteolytic systems. We attempted to establish any change of the protein concentrations of proteolytic system, since platelet proteasome concentrations have not been reported prior to our studies.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that a TAR-DNA/RNA binding protein (TDP-43) and its phosphorylated derivative (pTDP-43) levels were elevated in platelets obtained from AD patients as part of the blood-based biomarker development studies [13] . In this pilot study, we assessed the profile of target proteins for proteolytic machinery in platelet lysates obtained from AD patients and non-demented control subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is clear that AD is a disease of synaptic failure, the exact mechanisms causing neuronal dysfunctions and survival involve multiple aspects and remain to be determined. While aggregated Aβ is regarded as a catastrophic factor in AD pathogenesis, altered functions related to apolipoprotein E4 (ApoE4) [45,46], tau [30,47], α-synuclein [48,49], and TDP-43 (transactive response DNA binding protein 43 kDa) [50][51][52] are likely comorbidity factors. Other pathological factors such as inflammatory response, ion homeostasis disruption, oxidative stress, and decreased levels of neurotransmitters have also been identified and are considered to be sequential events of Aβ aggregation [53][54][55][56].…”
Section: Mediated Aβ Reduction As An Alzheimer's Disease (Ad) Therapymentioning
confidence: 99%
“…However, readers should be aware that there are some naturally occurring nonpathogenic amyloid-like fibril formations such as the nanostructure of certain bacteria [35] and the mammalian melanocyte integral membrane protein [36]. The pathogenesis of amyloidogenic proteinopathy may be initiated with amyloidogenic peptide fragments by one or more proteases [37]. Human amyloid pathologies known to require proteolytic processing of a precursor protein include AD where Aβ peptide fragments are liberated from a large APP precursor protein by β-and γsecretases [38].…”
Section: Proteolysis-generated Toxic Protein Speciesmentioning
confidence: 99%
“…The major representatives of such disorders are the amyloidoses, in which protein aggregation in the extracellular space is associated with the presence of malfunctioned protein molecules [37,90]. The chaperone-like small molecules may have the potential to be included in the treatment options for amyloidoses [91].…”
Section: Therapeutic Approach To Protein-misfolding Diseasementioning
confidence: 99%